Economies: An open access journal for the field of development macroeconomics - Ralf Fendel (Economies, 2013)
Economies (ISSN 2227-7099) is a new international, peer-reviewed open access journal for the academic fields of development economics and macroeconomics. While the latter seems to be clearly defined, development economics is not, because it is related to nearly all traditional economic sub-disciplines such as macroeconomics, international trade and finance, as well as microeconomics and public finance. Typically, academic field journals of development economics cover all those economic sub-disciplines. Economies instead focuses mainly on the macroeconomic perspective of economic development and it intends to publish academic research that is of strong macroeconomic policy relevance. In general, contributions in Economies should foster understanding of the macroeconomic process of economic development, with the process of development not exclusively being reserved to what we typically call developing countries. Also, the group of developed economies is still developing in the sense of improving their living standards further.
Keywords: 330